Antiferromagnetic transition of the caged compound TmTi2Al20. (18th March 2015) - Kase, Naoki; Shimura, Yasuyuki; Kittaka, Shunichiro; Sakakibara, Toshiro; Nakatsuji, Satoru; Nakano, Tomohito; Takeda, Naoya; Akimitsu, Jun
Abstract: We examined the low temperature magnetic properties of a single crystal of TmTi2 Al20, a hole analogue of PrTi2 Al20, by means of specific heat C ( T ) and magnetization M ( T, H ) measurements. At low field, an anomaly that can be ascribed to an antiferromagnetic ordering is observed in M ( T ) at T N = 0.7 K. C ( T ) shows a very sharp λ-type anomaly at 0.7 K, confirming the phase transition. From the calculated magnetic entropy S ( T ), we found that the ground state of TmTi2 Al20 is likely to be a magnetic Γ5 triplet in the J = 6 multiplet.